Genetic variations of human CYP2D6 in the Chinese Han population. (November 2013) - Qian, Jian-Chang; Xu, Xin-Min; Hu, Guo-Xin; Dai, Da-Peng; Xu, Ren-Ai; Hu, Li-Ming; Li, Fang-Hong; Zhang, Xiu-Hua; Yang, Jie-Fu; Cai, Jian-Ping
Aim: The purpose of this study was to determine the genetic polymorphisms of the CYP2D6 gene and to elucidate the allele distribution pattern in the Chinese Han population.Materials & methods: We used PCR and bidirectional sequencing methods to analyze all nine exons of the CYP2D6 gene in 2129 unrelated, healthy Chinese Han subjects from two geographical locations in China: the northern and southern regions.Results: In total, 165 mutated sites were detected in 2129 participants, of which 67 sites were reported for the first time. Among these novel mutation sites, 22 were nonsynonymous and 12 were named as novel alleles ( *87–*93, *94A, *94B and *95–*98 ) by the Human CYP Allele Nomenclature Committee. In addition, 29 previously reported alleles and 84 genotypes were also detected in 1954 volunteers. Functional prediction of novel variants revealed that eight variants might have a deleterious effect on CYP2D6. Linkage disequilibrium analysis and tagSNP selection were performed separately. By using these methods, distinct differences were found between the two regions.Conclusion: This study provides the most comprehensive data concerning CYP2D6 polymorphisms in the Chinese Han population to date and increases the number of known alleles; these findings may greatly contribute to the development of personalized medicine for the Chinese Han population. Original submitted 1 January 2013; Revision submitted 14 August 2013